Preparation and characterisation of layered metal hydroxides intercalated with ciprofloxacin and ethacrynic acid for slow drug release - Abdul Latip, Ahmad Faiz (2014)
In this study, two model drugs, ciprofloxacin (CFX) and ethacrynic acid (ECA) are intercalated in layered zinc hydroxides (LZH) and layered double hydroxides (LDH) host materials via either anion exchange or co-precipitation methods. Four intercalation compounds are obtained, designated as Z–CFX, AEZ–ECA, CPZ–ECA and MAL–ECA according to their materials and method of synthesis. Powder X-ray diffraction suggests that CFX and ECA were successfully intercalated in the interlayer region of their respective hosts, as indicated by the interlayer spacing expansion. The co-precipitation method gives a larger interlayer spacing value for CPZ–ECA compared to that of the anion exchange value in AEZ–ECA. This suggests the advantage of employing the former method over the latter in the intercalation of large organic molecule in the LMH hosts. Fourier transform infrared spectroscopy further confirms the intercalation of the CFX and ECA in the host interlayers when the absorption bands of carboxylate groups of the drugs emerge in the FTIR spectra, indicating both drugs were intercalated in an anionic form. The wavenumber differences of the carboxylate absorption bands reveal that the intercalated drugs were bonded to the metal cations of the host lattices via a unidentate coordination mode. Thermal analysis exhibits that the thermal properties of all the intercalated drugs were enhanced compared to that of the non-intercalated ones, possibly due to chemical interactions between the intercalated anionic drugs and the host lattices. A faster release behavior was demonstrated in phosphate-buffered saline (PBS) solution at pH 6.0 compared to that of pH 7.4. The release mechanisms are varied amongst the intercalation compounds, indicating different processes were involved during the release of the intercalated anions. The cytotoxicity was evaluated against VERO and A549 cell lines for 72 hours. The ECA–intercalated LMH compounds (AEZ–ECA, CPZ–ECA and MAL–ECA) were not toxic to both cell lines, whereas Z–CFX showed enhanced toxicity compared to that of the free CFX molecule. This study demonstrates the potentials of LMH materials as drug carriers based on the slow release behavior and the reduced toxicity profile of the intercalation compounds toward the VERO and A549 cell lines, especially concerning the ECA–intercalated LMH compounds.